2011
DOI: 10.1007/s11239-011-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective assessment comparing pharmacist-managed anticoagulation clinic with physician management using international normalized ratio stability

Abstract: To assess the rates of therapeutic international normalized ratio (INR) levels between pharmacist-managed clinics compared to traditional physician-management and to determine the variation in rates of therapeutic INR levels between pharmacist-managed clinic data compared to physician-management. Retrospective, randomized, chart review. Referral only, outpatient, pharmacist based anticoagulation clinic under a community based tertiary care health system. Sixty-four patients with at least 1 year's worth of visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…The remaining studies that assessed the impact of pharmacist‐managed anticoagulation clinic were all observational in nature. Similar to our results, all these studies reported substantial improvement in the anticoagulation care in the pharmacist‐managed model in comparison to the usual care [14,15,17,18,21]. Two of these studies have also assessed efficacy and safety outcomes and showed lower rates of thromboembolic events, bleeding events and emergency department visits, all of which led to significant reductions in cost [17,21].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The remaining studies that assessed the impact of pharmacist‐managed anticoagulation clinic were all observational in nature. Similar to our results, all these studies reported substantial improvement in the anticoagulation care in the pharmacist‐managed model in comparison to the usual care [14,15,17,18,21]. Two of these studies have also assessed efficacy and safety outcomes and showed lower rates of thromboembolic events, bleeding events and emergency department visits, all of which led to significant reductions in cost [17,21].…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have indicated that specialized anticoagulation clinics can reduce complications associated with inappropriate warfarin use and improve its efficacy [13]. A pharmacist‐managed anticoagulation clinic represents a model that provides patients with more consistent management, closer monitoring, more education and awareness especially in regards to interacting drugs and food that can alter warfarin efficacy and safety [12,14–16]. Previous studies including observational and randomized controlled trials have compared anticoagulation management provided by pharmacist‐based anticoagulation clinics to the usual doctor care [14,15,17–22].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist managed anticoagulation clinics are becoming common in hospitals of most countries and have shown improved patient outcomes including reduced hospital admissions for preventable embolism, bleeding, or treatment of thrombosis [16, 2527]. For example, implementation of a pharmacist managed ambulatory care anticoagulation clinic in South Korea resulted in an increase in percentage of INRs maintained within therapeutic range from 66% in the usual care group to 82% with the new initiative [28].…”
Section: Discussionmentioning
confidence: 99%
“…Ovaj parametar je odabran kao mera ishoda zato što predstavlja osnovni indikator efektivnosti i bezbednosti terapije varfarinom [19], i u skladu je sa ostalim relevantnim studijama [3,5,8,20,21].…”
Section: Verovatnoćeunclassified